PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN KINERJA KARYAWAN TERHADAP KEPUASAN KONSUMEN - RAHMAT RUDIYANTO (AKADEMIKA, 2021)
The purpose of this study was to determine and analyze partially and simultaneously the effect of the quality of human resources and employee performance on consumer satisfaction at Kasoem Hearing and Speech Center Malang. The population in this study were consumers who bought hearing aids at Kasoem Hearing and Speech Center Malang during the 2020 period, amounting to 208 people. Samples taken from the population (208 people) in this study were 137 people using the Slovin formula calculation and a margin of error of 5%. The data collection method used is through the distribution of questionnaires/questionnaires, the data analysis used is multiple linear regression. The results of this study prove the quality of human resources and employee performance partially and simultaneously have a significant influence on consumer satisfaction Kasoem Hearing and Speech Center Malang. The results of this study mean that consumer satisfaction is influenced by the quality of human resources and employee performance.